Decision optimization of machine sets taking into consideration logical tree minimization of design guidelines - Deptuła, Adam; Partyka, Marian (Zielona Góra: Uniwersytet Zielonogórski)
The method of minimization of complex partial multi-valued logical functions determines the degree of importance of construction and exploitation parameters playing the role of logical decision variables. Logical functions are taken into consideration in the issues of modelling machine sets. In multi-valued logical functions with weighting products, it is possible to use a modified Quine - McCluskey algorithm of multi-valued functions minimization. Taking into account weighting coefficients in the logical tree minimization reflects a physical model of the object being analysed much better.
Keywords: optimization; logical tree minimization; modified Quine - McCluskey algorithm; proportional valve